Viral Impact in Autoimmune Diseases: Expanding the “X Chromosome–Nucleolus Nexus” Hypothesis - Brooks, Wesley H. (Frontiers in Immunology, 2017)
Viruses are suspected of significant roles in autoimmune diseases but the mechanisms are unclear. We get some insight by considering demands a virus places on host cells. Viruses require production of their own proteins, RNA and/or DNA, but also production of additional cellular machinery, such as ribosomes, to handle the increased demands. Since the nucleolus is a major site of RNA processing and ribonucleoprotein assembly, nucleoli are targeted by viruses, directly when viral RNA and proteins enter the nucleolus and indirectly when viruses induce increased expression of cellular polyamine genes. Polyamines are at high levels in nucleoli to assist in RNA folding. The size and activity of nucleoli increase directly with increases in polyamines. Nucleolar expansion due to abnormal increases in polyamines could disrupt nearby chromatin, such as the inactive X chromosome, leading to expression of previously sequestered DNA. Sudden expression of a large concentration of Alu elements from the disrupted inactive X can compete with RNA transcripts containing intronic Alu sequences that normally maintain nucleolar structural integrity. Such disruption of nucleolar activity can lead to misfolded RNAs, misassembled ribonucleoprotein complexes, and fragmentation of the nucleolus. Many autoantigens in lupus are, at least transiently, components of the nucleolus. Considering these effects of viruses, the “X chromosome-nucleolus nexus” hypothesis, which proposed disruption of the inactive X by the nucleolus during stress, is now expanded here to propose subsequent disruption of the nucleolus by previously sequestered Alu elements, which can fragment the nucleolus, leading to generation of autoantigens.